Optimising the value of immunomodulatory drugs during induction and maintenance in transplant ineligible patients with newly diagnosed multiple myeloma: results from Myeloma XI, a multicentre, open‐label, randomised, Phase III trial. (12th July 2020) - Jackson, Graham H.; Pawlyn, Charlotte; Cairns, David A.; Striha, Alina; Collett, Corinne; Waterhouse, Anna; Jones, John R.; Wilson, Jamie; Taylor, Craig; Kishore, Bhuvan; Garg, Mamta; Williams, Cathy D.; et al.
Summary: Second‐generation immunomodulatory agents, such as lenalidomide, have a more favourable side‐effect profile than the first‐generation thalidomide, but their optimum combination and duration for patients with newly diagnosed transplant‐ineligible myeloma (ND‐TNE‐MM) has not been defined. The most appropriate delivery and dosing regimens of these therapies for patients at advanced age and frailty status is also unclear. The Myeloma XI study compared cyclophosphamide, thalidomide and dexamethasone (CTDa) to cyclophosphamide, lenalidomide and dexamethasone (CRDa) as induction therapy, followed by a maintenance randomisation between ongoing therapy with lenalidomide or observation for patients with ND‐TNE‐MM. CRDa deepened response but did not improve progression‐free (PFS) or overall survival (OS) compared to CTDa. However, analysis by age group highlighted significant differences in tolerability in older, frailer patients that may have limited treatment delivery and impacted outcome. Deeper responses and PFS and OS benefits with CRDa over CTDs were seen in patients aged ≤70 years, with an increase in toxicity and discontinuation observed in older patients. Our results highlight the importance of considering age and frailty in the approach to therapy for patients with ND‐TNE‐MM, highlighting the need for prospective validation of frailty adapted therapy approaches, which may improve outcomes by tailoring treatment to the individual.